Maternal high-fat diet impairs follicular development of offspring through intraovarian kisspeptin/GPR54 system - Zhiyang Zhou; Qi Lin; Xinxin Xu; Gaby Sukma Illahi; Chenle Dong; Xueqing Wu (BMC, 2019)
Abstract Background Excessive gestational weight gain (GWG), which is associated with adverse long-term effects on the health of the offspring, has become a major clinical problem. Accumulating evidence indicates that the ovary kisspeptin/GPR54 system directly participates in a series of physiological activities. We used a model of high-fat diet (HFD) during gestational to investigate offspring's ovarian function and whether kisspeptin/GPR54 system is involved. Methods After introducing the male and confirmation of mating by checking a vaginal sperm plug, female rats were randomized into two groups: control diet called NCD group and high-fat diet called HFD group. After birth, all rats were changed into a control diet and litter size was adjusted to 12 pups per litter. Ovaries were collected for assessment at postnatal day (PND) 4 and PND 30. The timing of vaginal opening was recorded, and the estrous cyclicity was monitored for 2 consecutive weeks immediately. Primary granulosa cells and ovaries which were taken from PND 4 were collected for determination of the direct effect of kisspeptin-10 (kp-10) in vitro. Results Neonatal rats exposed to HFD during gestation had a lower number of secondary follicles in the ovary. The expression of follicle-stimulating hormone receptor (FSHR) and kisspeptin was not altered. At prepuberty, the number of antral follicles and preovulatory follicles was elevated with decreased type III follicles in the HFD group. While the expression of ovulation-related genes was decreased, the expression levels of follicular growth-related genes and steroidogenesis synthesis related genes were elevated. A significant increase in kiss1 mRNA and kisspeptin protein was detected without changes in kiss1r mRNA and GPR54. Maternal high-fat diet during gestation resulted in a significant advanced puberty onset and an irregular estrous cycle in offspring rats. In addition, the administration of kp-10 produced an increase in viability of primary granulosa cells and enlarged the size of oocytes. Conclusions HFD exposure during maternal gestation had a long-term effect on reproductive function in the offspring and the increased ovarian kisspeptin/GPR54 system might be involved.